Beginning Google Blogger - Wright-Porto, Heather; Anglin, Steve; MacDonald, Brian; Andres, Clay.; Beckner, Mark.; Buckingham, Ewan.; Campbell, Tony.; Cornell, Gary.; Gennick, Jonathan; Lowman, Michelle; Moodie, Matthew; Pepper, Jeffrey; et al. (Berkeley, CA : Apress, 2010)
Are you interested in starting a blog but can$1 (Bt decide on which service to use? Google$1 (Bs Blogger offers many advantages over other blog publishing systems, including seamless integration with Google services and web applications. Beginning Google Blogger is a complete resource on how to create and manage a blog using Blogger. The book offers step-by-step instructions and visual aids which walk you through both the basics of Blogger and the advanced features it offers$1 (Bfrom creating a new blog and choosing fonts and colors, and installing custom blog graphics; to converting from a 2-column to a 3-column layout, setting up a domain name and creating an online store with a built-in navigational bar. The journey from newbie to experienced blogger will be fun and challenging. You$1 (Bll learn practical applications of the most popular gadgets, search engine optimization tips, how to make money using Blogger, and, overall, taking blogging to a new level by incorporating social networking tools, using advanced blog design techniques, setting up a custom domain and creating an online store.s
Getting Started -- Blog Layout and Design -- Making the Most of Your Blog -- Setting Up a Custom Domain -- Working with Images -- Advanced Design and Layout -- Setting Up a Blog Store -- Troubleshooting and Blog Help.
Keywords: Computer science; Multimedia systems; Computer Science; Multimedia Information Systems